2022
DOI: 10.3389/fgene.2022.862105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Diagnostic and Prognostic Biomarkers for Gastric Cancer Based on Bioinformatic Analysis

Abstract: Background: Gastric cancer (GC) is one of the most prevalent cancers all over the world. The molecular mechanisms of GC remain unclear and not well understood. GC cases are majorly diagnosed at the late stage, resulting in a poor prognosis. Advances in molecular biology techniques allow us to get a better understanding of precise molecular mechanisms and enable us to identify the key genes in the carcinogenesis and progression of GC.Methods: The present study used datasets from the GEO database to screen diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Additionally, in the liver, GLT8D2 can positively regulate the expression of the ApoB100 protein in hepatocytes, promote the stable secretion of very low density lipoprotein and reduce the accumulation of triglycerides in hepatocytes, thus reducing the incidence of non-alcoholic fatty liver disease (NAFLD) ( 53 ). SPARC has been previously reported as a potential target in GC ( 54 , 55 ). The high expression of VCAN can be used as an independent predictor to indicate the adverse outcome of GC ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the liver, GLT8D2 can positively regulate the expression of the ApoB100 protein in hepatocytes, promote the stable secretion of very low density lipoprotein and reduce the accumulation of triglycerides in hepatocytes, thus reducing the incidence of non-alcoholic fatty liver disease (NAFLD) ( 53 ). SPARC has been previously reported as a potential target in GC ( 54 , 55 ). The high expression of VCAN can be used as an independent predictor to indicate the adverse outcome of GC ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stickler syndrome type II is caused by COL11A1 gene mutations ( Vogiatzi et al, 2018 ). Previous bioinformatics analysis has demonstrated that COL5A2, COL10A1, and COL11A1 may be used as a diagnostic or prognostic biomarker for tumors such as gastric cancer ( Niu et al, 2022 ), breast carcinoma ( Giussani et al, 2018 ), and non-small-cell lung cancer ( Andriani et al, 2018 ). According to the findings of RNA sequencing, COL5A2, COL10A1, and COL11A1 have been reported to be upregulated in keloid ( Bi et al, 2021 ; Lin P. et al, 2022 ), as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The other four genes (COL1A2, COL4A1, SPARC and CEP55) are related to the prognosis of GC, which mainly encode collagen, acidic matrix related protein and centrosome protein of GC cells. The previous studies have found that collagen-encoding genes COL1A1 and P4HA3 may be related to the prognosis of GC[ 35 ]. At the present study, we found that COL4A1 and COL1A2 may have some effects on extracellular matrix and its interaction with receptors, protein binding, protein digestion and absorption, and regulate PI3K Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%